2012
DOI: 10.3109/09638288.2012.715720
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a child with severe intellectual disability in China: The example of Rett syndrome

Abstract: Implications for rehabilitation Little is known about the lives of girls with Rett syndrome in China, a genetic condition associated with severe disability.  Most girls experienced home-based care with limited access to appropriate equipment, education and rehabilitation.  Limited information and discrimination and stigma from some community members reduced families' abilities to meet their child's needs.  Greater access to health, education and information services in China should be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
3
13
2
Order By: Relevance
“…In this way, relevant information was collected from the caregivers’ perspective. The question guide was developed based on a prior literature review [6,7,8,9,10,11,12,13] and the researchers’ experience [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, relevant information was collected from the caregivers’ perspective. The question guide was developed based on a prior literature review [6,7,8,9,10,11,12,13] and the researchers’ experience [16].…”
Section: Methodsmentioning
confidence: 99%
“…The experience and individual perspective of the caregivers concerned is relevant, just as one’s life experiences, ambitions and emotional needs should be considered when treating children with RTT [3,8,9,10,11,12,13]. Therefore, several questions remain unanswered: how do caregivers live and care for their children with RTT?…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to include this dimension of behavioral phenotype severity in understanding family members' well-being. The extent of the health problems of individuals with Rett syndrome has also been associated with maternal wellbeing in quantitative (Byiers et al 2014) and qualitative research (Lim et al 2013). Data on behavioral phenotype severity and health problems need to be collected alongside a third factor that has been consistently and pervasively associated with parental well-being.…”
Section: Introductionmentioning
confidence: 98%
“…Lim et al (2013) interviewed 14 mothers of individuals with Rett syndrome in China and found that families had significant needs for support with their relative's health problems. In a survey study, Mulroy et al (2008) asked parents of individuals with Rett or Down syndromes about sibling experiences in the families.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to professionals and family members, society needs information about the capabilities of people with RTT and the changes that occur at different stages. Lim et al21 conducted a qualitative study exploring the daily experiences of families caring for children with RTT and found participants reporting a lack of education and rehabilitation and support services available to them. Those families reported that limited access to information reduced families’ capacity to adequately meet the needs of their child.…”
Section: Introductionmentioning
confidence: 99%